Anemia in Chronic Kidney Disease : Role of Hypoxia Inducible Factor Stabilizer - Emilia; Zulkhair Ali (HM Publisher, 2021)
Anemia contributes to increased morbidity and mortality in chronic kidney disease patients. The pathogenesis of anemia in these patients is multifactorial, but the contribution of erythropoietin deficiency becomes greater as glomerular filtration rate declines which related to decreased nephron mass. The current standard of care includes supplemental iron, erythropoiesis-stimulating agents (ESA), and red blood cell transfusions, although each has drawbacks. Lately, concern has arisen following randomized clinical trials showing that higher hemoglobin targets and/or high ESA doses may cause significant harm including increasing cardiovascular and thrombotic events, and even death. Recent experimental and clinical studies show the promising efficacy of hypoxia inducible factor (HIF) stabilizer which stimulates endogenous erythropoietin production and enhance iron availability.